Comparative protection of small ruminants against Mannheimia haemolytica infection by inactivated bacterin and toxoid vaccines - Dounia Bkiri; Soufiane Elmejdoub; Zahra Bamouh; Ouafaa Fassi Fihri; Mehdi El-Harrak (Veterinary World, 2023)
Background and Aim: Mannheimia haemolytica causes respiratory infection and mortality in sheep and goats, similar to the effects in cattle, which causes major economic damage. Regular vaccinations alongside good management practices remain the most efficient tools for controlling this disease. Indeed, vaccines against pasteurellosis are available, but results on their efficacy have varied. Therefore, this study aimed to evaluate the efficacy of three vaccines against mannheimiosis in small ruminants.